2018
DOI: 10.19090/pp.2018.3.285-300
|View full text |Cite
|
Sign up to set email alerts
|

Relacije Bavljenja Sportom I Emocionalne Inteligencije Na Srednjoškolskom Uzrastu

Abstract: Istovremeno vrlo popularan i metodološki kontroverzan konstrukt emocionalne inteligencije je dovođen u vezu sa velikim brojem relevantnih eksternih varijabli kada je u pitanju psihološko funk- cionisanje u različitim životnim domenima. Iako postoje teorijska razmatranja koja povezuju bavljenje sportom sa izraženošću emo- cionalne inteligencije, mali je broj empirijskih istraživanja te veze, a ona su pogotovo rijetka na našem podneblju i kada je u pitanju ado- lescentska dob. Cilj našeg istraživanja je bio ispi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Kopp and Crombie [33,34] even proposed EI as a predictor of sports performance. Some researchers have proposed comparative studies between athletes and non-athletes, finding that athletes have significantly higher EI than non-athletes [35,36]. The same differences have specifically also found in female athletes and non-athletes [37,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kopp and Crombie [33,34] even proposed EI as a predictor of sports performance. Some researchers have proposed comparative studies between athletes and non-athletes, finding that athletes have significantly higher EI than non-athletes [35,36]. The same differences have specifically also found in female athletes and non-athletes [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, studies have compared individuals who achieved PA recommendations vs. those who do not [9,19], those who practise sport vs. those who do not [35,36], or EI levels according to the type of sport [20,51]. In many cases, it was concluded that both PA and sport are appropriate mediums for the work and development of EI.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies into the difference in EI among athletes and non-athletes ( Costarelli and Stamou, 2009 ; Szabo and Urban, 2014 ; Lepir et al, 2018 ). These studies found that athletes have greater EI than non-athletes, specifically in terms of assertiveness, understanding their own emotions, appraising others, and controlling their emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existing research, various aspects of the relationship between sports experience and EI remain unclear ( Costarelli and Stamou, 2009 ; Kajbafnezhad et al, 2011 ; Ghaderi and Ghasemi, 2012 ; Laborde et al, 2014 , 2017 ; Saies et al, 2014 ; Szabo and Urban, 2014 ; Castro-Sánchez et al, 2018a , b ; Lepir et al, 2018 ; Vaughan et al, 2019 ). The type of sport, time spent practicing (frequency days/week, years of practice), the number of different sports practiced, and the highest competitive level achieved are all characteristics of sports experience that may be related to EI.…”
Section: Introductionmentioning
confidence: 99%
“…Ako je nešto naučeno iz krize reproducibilnosti to je da statistička analiza ne smije počivati na samo jednom, automatizovanom kriterijumu kao što je to unazad nekoliko decenija bio slučaj. U vezi s tim predlaže se da se BF koristi zajedno sa P-vrijednostima ; primjeri na našem prostoru Lepir, Lakić i Takšić, 2018, ili Mirković & Lakić, 2019 ili zajedno sa testom ekvivalentnosti koji i zasebno predstavlja smisleniji modus od P-vrijednosti . Realno gledajući, ranije jesu postojale tehničke prepreke za korištenje BF u smislu da su softverska rješenja bila nedostupna, ali danas takvih prepreka nema.…”
Section: Zaključakunclassified